Actor diversity and interactions in the development of banana hybrid varieties in Uganda: implications for technology uptake - Sanya, L.N.; Sseguya, H.; Kyazze, Florence Birungi; Baguma, Y.; Kibwika, P. (Informa UK Limited, 2018)
Purpose: We examine the nature of networks through which new hybrid banana varieties (HBVs) in Uganda are developed, and how different actors engage in the technology development process.